2004
DOI: 10.1097/01.pcc.0000102225.49058.4b
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of red blood cell transfusion through small bore central venous catheters used in neonates

Abstract: No clinically significant hemolysis was evidenced with red blood cell transfusion through small-bore central venous catheters when using fresher or older CPDA-1 red blood cells at 2 or 20 mL/hr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…It is important to note that when the transfusion rate was slower than the rapid manual push (e.g., 2 mL/min), our results showed only minimal increased hemolysis using the one‐way valve. At least one previous study using a syringe pump and small‐bore central venous catheter found no significant hemolysis with flow rates up to 20 mL/hr . However, another report described significant hemolysis using catheters smaller than 22‐gauge and manual syringe push .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that when the transfusion rate was slower than the rapid manual push (e.g., 2 mL/min), our results showed only minimal increased hemolysis using the one‐way valve. At least one previous study using a syringe pump and small‐bore central venous catheter found no significant hemolysis with flow rates up to 20 mL/hr . However, another report described significant hemolysis using catheters smaller than 22‐gauge and manual syringe push .…”
Section: Discussionmentioning
confidence: 99%
“…At least one previous study using a syringe pump and small-bore central venous catheter found no significant hemolysis with flow rates up to 20 mL/hr. 14 However, another report described significant hemolysis using catheters smaller than 22-gauge and manual syringe push. 8 High and nonuniform pressures during rapid manual transfusion may contribute to increased Hct Change in Hct * The time required for simulated transfusion of 4.5 mL of RBCs was measured using a manual stopwatch for 2 of the 3 units tested by manual simulated transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the average time of erythrocyte storage was seven and a half days, ranging from one to 25 days. According to researchers, the period of storage of red blood cells of up to ten days is considered short, and the erythrocytes, consequently, considered young, while the period above 25 days is considered prolonged (13) .…”
Section: Peripherally Inserted Central Catheter Obstruction In Packed...mentioning
confidence: 99%
“…Existing evidence on erythrocyte transfusion in the PICC and its relationship with occurrence of obstruction are rare. When performed, the studies are directed to tests in laboratory to relate the occurrence of hemolysis with the rate of infusion of the blood, catheters and equipment used for infusion (12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%
“…However, some people prefer to reserve these catheters for nutrient solutions or drugs because of concerns about clogging a small-bore central catheter with a blood transfusion. 1 Hence, small peripheral needles are often used for transfusions.…”
Section: Venous Accessmentioning
confidence: 99%